2018
DOI: 10.1111/cea.13247
|View full text |Cite
|
Sign up to set email alerts
|

Identification of gibberellin‐regulated protein as a new allergen in orange allergy

Abstract: Orange GRP may be involved in orange allergy and may be a cross-reactive allergen between citrus fruits and the Rosaceae family of fruits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 35 publications
0
27
0
3
Order By: Relevance
“…Although cypress trees are typical of Mediterranean regions, Cupressaceae pollen dispersal also affects non‐Mediterranean environments, including Central Europe, North America, Mexico and Japan . GRP‐related allergy to Rosaceae and Citrus fruits was reported in conjunction with Japanese cedar pollinosis . In south‐central United States, mountain cedar ( Juniperus ashei ) pollen is a major cause of allergic rhinoconjunctivitis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although cypress trees are typical of Mediterranean regions, Cupressaceae pollen dispersal also affects non‐Mediterranean environments, including Central Europe, North America, Mexico and Japan . GRP‐related allergy to Rosaceae and Citrus fruits was reported in conjunction with Japanese cedar pollinosis . In south‐central United States, mountain cedar ( Juniperus ashei ) pollen is a major cause of allergic rhinoconjunctivitis .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we found that Pru p 7 sensitization was associated with reactions to an array of plant foods, including but not limited to Rosaceae . Members of the GRP family are widely distributed in the plant kingdom, share high levels of sequence identity and have been associated with particularly severe food allergic reactions in at least three environments: Italy, France and Japan …”
Section: Discussionmentioning
confidence: 99%
“…Thisprotein is not yet commercially available for the in-vitro diagnosis of GRP-induced pollen-food allergy syndrome. Other foods have been reported to be potential inducers of allergic reactions in patients hypersensitive to this family of allergens, including Japanese apricot [12], orange [13], and pomegranate [14], the names of these allergens being Pru m 7, Cit s 7, and Pun g 7, respectively. Further, clinical reactivity against apple, melon, watermelon, and strawberry [2], as well as to exotic fruits, kiwi, tomato, fig, carrot, grapes, coconut, and celeriac [15] has been reported in Pru p 7-hypersensitive patients making GRP a potential novel plant-food panallergen.…”
Section: Introductionmentioning
confidence: 99%
“…On les trouve aussi bien dans la peau que dans la pulpe du fruit. Des homologues sont décrits dans divers aliments d'origine végétale : la pêche, l'orange (Cit s 7) [13], la grenade (Pun g 7 : pommaclein) [11], l'abricot du Japon (Pru m 7), ainsi que dans le tubercule de pomme de terre [9].…”
Section: Introductionunclassified